Pharmacists' perceptions and attitudes toward drug importation into the State of Florida - John B. Hertig; Jade M. Jochem; Allissa M. Long (Taylor & Francis Group, 2021)
Background The Department of Health and Human Services and the Food and Drug Administration released the Safe Importation Action Plan in July 2020 detailing methods to import medicines from Canada to combat increasing drug costs. In November 2020, Florida became the first state in the United States to create and propose an importation plan from Canada. This study examines the proposal submitted by Florida, Florida pharmacists' perceptions of the program on patient safety, and Florida pharmacists' thoughts on the pharmacy operational impact. Methods This was a cross-sectional study utilizing an electronic questionnaire sent to pharmacist members of the Florida Pharmacy Association. The survey incorporated closed-ended and open-ended questions. The results from the study were reported and analyzed through descriptive statistics, qualitative and quantitative data. Results Two-hundred and forty-four pharmacists responded to the survey. Of those respondents, 25% stated they had no knowledge about Florida's drug importation plan. Less than 12% of respondents stated they would trust the safety and quality of imported medicines. Seventy percent of pharmacists expressed concerns regarding the changes required in pharmacy operations to increase medicine safety. About half of the respondents questioned whether this plan would promote cost-savings as intended. Conclusion Florida pharmacists believe the drug importation plan does not address all aspects of patient and medicine safety and expressed concerns regarding logistical operations of a pharmacy. This article highlights those concerns and acts as a summons to action.